Strategi Efektif dalam Merancang dan Mengevaluasi Kinerja Pekerjaan di Era Manajemen Kontemporer - Madaniyah, Madaniyah; Sohiron, Sohiron (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
In the contemporary organizational management landscape, job performance design and evaluation has become a major factor influencing organizational effectiveness and employee well-being. The application of advanced technologies such as FP-Growth and K-Means algorithms allows businesses, especially online stores, to adjust sales strategies based on consumer purchasing patterns, increasing operational efficiency and strategy relevance. Additionally, the use of methodologies such as the Balanced Scorecard and Analytical Network Process (ANP) provides a holistic performance evaluation framework, covering both financial and non-financial aspects, helping organizations identify areas of improvement and strategic alignment. Fair reward strategies and transformational leadership roles are proven to increase employee motivation and performance, while recognition of individual differences allows for adjustments in management approaches to create an inclusive and productive work environment. This research adopted a mixed methods approach to evaluate the impact of job design on employee performance, focusing on teachers in the Kalmunai Zone. Through surveys, interviews, and regression analysis, this research aims to provide a comprehensive understanding of the relationship between job design and employee performance. By integrating technology, a holistic approach and human-centered leadership, organizations can achieve sustainable and superior performance amidst dynamic changes in today's business landscape